ILMU KANURAGAN AT ROHMATUL UMMAH ASSALAFY PESANTREN OF JEKULO KUDUS - Mukhamad Rikza (Al-Albab, 2013)
Pesantren are one source of knowledge, especially in Indonesia. Almost in every district in Java region in particular there is a boarding school, from which inhabited tens to thousands of students. The style of education offered also varied, from the shape of the Salaf to modern. There is also a yellow book offers study programs in an effort to preserve the concept of shariah brought by salaf scholars who in fact are the inheritors of the prophets. In addition to studying the book of yellow, there is also a boarding school who study science kanuragan (supernatural power) or martial arts. All have their respective advantages which aims to preserve Islamic values berasas on the Qur’an and hadith. Yellow Book and science kanuragan into a Pesantren tradition that can not be released. Science kanuragan very beneficial, especially before the independence of Indonesia. Therefore, the students participate in running the missions and fight against criminals and invaders. Science kanuragan , when it plays a lunch the students to fight for independence and the provision of da’wah. Teaching science kanuragan felt to be more urgent for the “protection” in the face of the enemy. At that science to be excellent kanuragan interesting to study. Keywords: ilmu kanuragan, pesantren, Jekula kudus